Practical Robust Fixed-Time Speed Control of Permanent Magnet Synchronous Motors with Adaptive Disturbance Rejection - Napasool Wongvanich; Varin Cholahan; Worapong Tangsrirat (My University, 2025)
The research presents an adaptive fixed-time speed controller of Permanent Magnet Synchronous Motors for a second-order nonlinear systems, grounded in practical fixed-time stability (CFTSMC). This approach employs a sliding mode surface with constant exponent coefficient designed to circumvent singularities and achieve a rapid convergence. Compared to more complex fixed-time controller, this method offers ease to implement. In addition, the maximum limits for control inputs are simply determined to avoid saturation problems. Subsequently, the stability of nonlinear speed control system is analyzed using well-kwon nonlinear Lyapunov technique. An adaption algorithm called adaptive disturbance rejection (ADR), is incorporated with a smooth tanh function to mitigate overall disturbances and chattering, thereby ensuring that the tracking error stays within a bounded residual region. Ultimately, numerical simulations are provided to demonstrate the efficacy of both controller and disturbance rejection approach.
Keywords: Sensorless Control of Electric Motors; Electric Motor Design and Analysis; Iterative Learning Control Systems